2017
DOI: 10.1186/s40462-017-0100-6
|View full text |Cite
|
Sign up to set email alerts
|

A few long versus many short foraging trips: different foraging strategies of lesser kestrel sexes during breeding

Abstract: BackgroundIn species with biparental care both members of the breeding pair cooperate to raise the offspring either by assisting each other in every reproductive task or by specializing in different ones. The latter case is known as reproductive role specialization. Raptors are considered one of the most role-specialized groups, but little is known about parental behavior away from the nest. Until the advent of biologgers, avian role specialization was traditionally studied with direct observations at the nest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 79 publications
2
15
0
Order By: Relevance
“…When they are in a favourable habitat, the flight distances are lower (Bustamante 1997;Tella et al 1998;Catry et al 2013), and in our study the frequency of locations at greater distances from the nest is higher in the thermosolar power plant colony, with also greater distances than those of the individuals from the other colony (located in a natural landscape) before July 15, when they need more quantity of preys to feed the chicks. Coinciding with Vlachos et al (2015), we have not observed differences in the foraging areas and distances to the nest between sexes, although other studies have found a spatial segregation, with males foraging closer to the colony than females (Hernández-Pliego et al 2017).…”
Section: Discussionsupporting
confidence: 89%
“…When they are in a favourable habitat, the flight distances are lower (Bustamante 1997;Tella et al 1998;Catry et al 2013), and in our study the frequency of locations at greater distances from the nest is higher in the thermosolar power plant colony, with also greater distances than those of the individuals from the other colony (located in a natural landscape) before July 15, when they need more quantity of preys to feed the chicks. Coinciding with Vlachos et al (2015), we have not observed differences in the foraging areas and distances to the nest between sexes, although other studies have found a spatial segregation, with males foraging closer to the colony than females (Hernández-Pliego et al 2017).…”
Section: Discussionsupporting
confidence: 89%
“…Previous work has examined species‐level differences in movement patterns, including differences in home‐range size (Haskell, Ritchie, & Olff, ) and migration distances/strategies (Alerstam, Hedenström, & Åkesson, ; La Sorte et al, ) based on species‐level traits (e.g., body size and diet). Some of the variation among individuals within the same species is probably attributable to sex, because males and females have different movement patterns during brood rearing (Hernández‐Pliego, Rodríguez, & Bustamante, ). In addition, feather moult (i.e., feathers being shed and regrown) may impact avian movements, including periods of flightlessness (e.g., cranes and waterfowl post‐breeding) and reduced aerodynamic performance of the wings (e.g., Falco peregrinus ; Flint & Meixell, ).…”
Section: Discussionmentioning
confidence: 99%
“…False positives were none or negligible for gulls and storks (0 and 2% respectively), but reached 50% for kestrels. This is likely explained by species-specific behavior: kestrels spend long stretches of time and consecutive days on a perch while scanning for prey or resting [37]. Distinguishing these patterns of attendance and revisitation from those of a nest might be challenging without applying restrictions based on seasonality and geographical area (for instance, breeding versus wintering range).…”
Section: Performance Of Nest-site Detectionmentioning
confidence: 99%
“…In this case, our inability to recognize the attempt as successful might have depended on behavioral differences between parents, whereby the male we were tracking might have interrupted parental care before the female did. This result highlights the importance of taking into account sex differences in breeding behavior, where that applies [37]. For example, in species exhibiting uniparental care, inference should only be based on the sex that carries out parental care [8].…”
Section: Performance Of Reproductive Fate Estimationmentioning
confidence: 99%